Measles Morbidity and Mortality in the Department of Child Health, Dr. Pirngadi General Hospital, Medan, in 1973-1977 - S. M. Rangkuti; Nasril Nazir; A. H. Sutanto; Aswin Lubis; Helena Siregar (Indonesian Pediatric Society, 1980)
One hundred seventy-six cases with measles have been hospitalized at the Department of Child Health, Dr. Pirngadi General Hospital, Medan in 1973 - 1977. The case fatality rate was 26.1%. The most frequent complications found were Pneumonia, Encephalitis, Diarrhea and Dehydration. Age specific mortality, as expected, was highest in the 0 - 1 year age group (38.6%). A high proportion of the survivors (22.2%) showed recidual signs of brain damage and blind-ness. This study proved that active immunization against measles in Indonesia must have priority.